Solving Quantum Mechanics Problems Via Integral Rohit Transform - Rohit Gupta; Rahul Gupta; Dinesh Verma (Kirkuk Journal of Science)
This solves quantum physics problems using the integral Rohit transform, including the scattering of low energy particles by a completely rigid sphere and particle behavior in a one-dimensional infinitely high potential box. The standard calculus approach is typically used to solve these quantum mechanics issues. To solve these quantum physics challenges, this research presents a new method: the integral Rohit transform. When compared to other approaches that are currently in the literature, the obtained solutions show how accurate the suggested method is. This demonstrates the potential and efficacy of the suggested approach to overcoming quantum mechanical issues, such as low-energy particle scattering by a completely rigid sphere and particle behavior in a one-dimensional infinitely high potential box. In this paper, the successful application of the integral Rohit Transform has been demonstrated in solving the one-dimensional time-independent Schrodinger's equation. This application has yielded results that include the determination of eigen energy values and eigen functions for a particle confined within an infinitely high potential well, as well as the calculation of the total scattering cross-section for low energy particles interacting with a perfectly rigid sphere. In the case of low energy limit, the total scattering cross-section for low energy particles due to a perfectly rigid sphere, as determined through quantum mechanics, is equivalent to the geometrical cross-section of said sphere. Additionally, the energy values that the particle can possess within a 1d infinitely high potential well demonstrate that the energy of said particle, when confined within this potential well, is quantized.